Metode Pelaksanaan Pekerjaan Struktur Balok dan Pelat Lantai 2 Pembangunan Gelanggang Generasi Muda Majalengka - Nawawi, Khaeril Anwar; Arief Rijaluddin (Universitas Majalengka, 2024)
Beams and Floor Plates are a very important construction structure in a building. In carrying out work on floor slabs and beams, a method is needed to complete the work in the field. Especially when facing obstacles caused by field conditions that do not match previous expectations. For this reason, applying construction implementation methods that are appropriate to field conditions will be very helpful in the process of completing construction projects. Research on the construction method for the beam and floor slab construction was carried out at the Majalengka Young Generation Center construction. The casting method for the beams and floor slabs is conventional using ready mix concrete with a slump test value of 12 ± 2. From the results of the research on the construction implementation method for the Majalengka Young Generation Arena, it was found that: beam and floor plate work includes, preparatory work includes measuring work, scaffolding installation and formwork installation, then there is reinforcement/reinforcing work, namely steel fabrication in the project area, then there is work Casting the beams and floor plates using a tower crane. Next, maintenance work is carried out on the concrete mixture during the drying process, namely by watering according to regulations.